INFLUENCE OF IMPURITIES IN NATURAL SEEDS OF ALFALFA AND RED CLOVER ON THE SEED CLEANING PROCESS - Djokic, Dragoslav (Journal on Processing and Energy in Agriculture, 2021)
The paper presents the results of the cleaning process of five different lots of natural alfalfa seeds and five different lots of natural red clover seeds. Natural alfalfa and red clover seeds had 75 % to 77 % purity. The experiment was performed in the seed processing center of the Institute for Forage Crops Kruševac. The seeds for sowing must be with high purity, high germination and genetic value. Seed cleaning is performed on different machines that work on the principle of differences in the physical properties of seeds. Significant parameters that define the quality of seeds after processing on the cleaning equipments are: the amount of pure seed, weed seed, the seed of other crops, inert matter, amount of pure processed seed, seed losses and processing output. The obtained results enable the correct adjustment of the equipment for the seed processing, depending on the amount and type of weeds and other impurities found in the natural seed of alfalfa and red clover.